2015
DOI: 10.3892/ol.2015.3114
|View full text |Cite
|
Sign up to set email alerts
|

Amplification and protein expression of androgen receptor gene in prostate cancer cells: Fluorescence in situ hybridization analysis

Abstract: Abstract. Prostate cancer (PCa) is the most frequently diagnosed non-skin cancer and the second highest cause of cancer-related mortality in adult males worldwide. PCa is highly dependent upon androgen receptor (AR) signaling for cell proliferation and survival. The AR therefore plays a vital role in the develop ment and function of normal and malignant prostate cells or PCa recurrence. The present study aimed to examine the ubiquity of AR amplification in PCa recurrence, even in the absence of androgen. For t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 20 publications
(19 reference statements)
1
8
0
Order By: Relevance
“…reported that 62.7% of AR aberrations and 71.3% of AR pathway aberrations were identified in 150 mCRPC patients [45]. This is consistent with recent study on a larger cohort that demonstrated the potential contribution of AR amplification to AR activation [48]. …”
Section: Discussionsupporting
confidence: 87%
“…reported that 62.7% of AR aberrations and 71.3% of AR pathway aberrations were identified in 150 mCRPC patients [45]. This is consistent with recent study on a larger cohort that demonstrated the potential contribution of AR amplification to AR activation [48]. …”
Section: Discussionsupporting
confidence: 87%
“…Prostate cancer is the most common malignancy in American men 1 2 . Although localized prostate cancer is curable by surgery, the primary treatment for metastatic prostate cancer remains androgen deprivation therapy (ADT).…”
mentioning
confidence: 99%
“…During the progression of PCa from primary to CRPC, several changes occur to the AR and AR signaling pathway that could provide an explanation for the CRPC mechanism. The most common genetic change in CRPC patients is AR gene amplification [98], which accounts for more than 80% of CRPC patients. A further study based on the fluorescence in situ hybridization (FISH) technique demonstrated that no AR amplification was observed in benign prostate hyperplasia, and just 2% was detected in primary PCa tumors.…”
Section: Mechanism Of Castration-resistant Prostate Cancer (Crpc)mentioning
confidence: 99%